(i) The sum of the first three terms of a geometric series is equal to 15 and the sum of the next three terms is equal to \( -\frac{15}{8} \). Calculate the sum of the first 8 terms of this series.
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
Let the first term of the geometric series be \( a \) and the common ratio be \( r \). The first three terms are: 1. \( a \) 2. \( ar \) 3. \( ar^2 \) The sum of the first three terms is given by: \[ a + ar + ar^2 = 15 \] Factoring out \( a \), we have: \[ a(1 + r + r^2) = 15 \quad \text{(1)} \] Next, the next three terms are: 4. \( ar^3 \) 5. \( ar^4 \) 6. \( ar^5 \) The sum of these three terms is: \[ ar^3 + ar^4 + ar^5 = ar^3(1 + r + r^2) = -\frac{15}{8} \quad \text{(2)} \] From (2), substituting (1): \[ ar^3 \cdot \frac{15}{a} = -\frac{15}{8} \] This simplifies to: \[ r^3 \cdot 15 = -\frac{15}{8} a \implies r^3 = -\frac{1}{8} a \] Now from (1), substituting \( a \) in terms of \( r \): \[ a(1 + r + r^2) = 15 \implies a = \frac{15}{1 + r + r^2} \] Substituting for \( a \) in \( r^3 = -\frac{1}{8} a \): \[ r^3 = -\frac{1}{8} \cdot \frac{15}{1 + r + r^2} \] \[ r^3 (1 + r + r^2) = -\frac{15}{8} \] Multiplying through by \( 8 \) gives: \[ 8r^3 (1 + r + r^2) = -15 \] Let’s express \( r^3(1 + r + r^2) \): 1. Expanding \( 8r^3 + 8r^4 + 8r^5 = -15 \) 2. Rearranging gives \( 8r^5 + 8r^4 + 8r^3 + 15 = 0 \). We can substitute \( r \) in small rational guesses or seek roots with the Rational Root Theorem. Testing \( r = -\frac{1}{2} \): \[ 8\left(-\frac{1}{2}\right)^5 + 8\left(-\frac{1}{2}\right)^4 + 8\left(-\frac{1}{2}\right)^3 + 15 = 0 \] \[ -1 + 0 + 1 + 15 = 15 \text{ (which isn't zero)} \] Trying more values will lead us to a valid ratio if probing. After solving, we calculate \( S_8 \): The sum of the first \( n \) terms of the geometric series is: \[ S_n = a \frac{1 - r^n}{1 - r} \] Here, \( S_8 = a \frac{1 - r^8}{1 - r} \). Using found values, you can compute it to yield for specific results of \( S_8 \) in \( a, r \) forms.